Cloud-Based Data Governance: Ensuring Security, Compliance, and Privacy - Naik, Shivali (The Eastasouth Journal of Information System and Computer Science, 2023)
Cloud computing has been taken up very rapidly and has over time changed the way an organization stores, processes, and shares data towards much higher levels of efficiency, scalability, and innovation. This paradigm shift, however, bears its unique and very complex challenges towards security of data and network security. Since sensitive in- formation finds its storage and transmission increasingly on shared multi- tenant cloud environments, the potential for data breaches, unauthorized access, and other cyber threats becomes much more viable. Moreover, the shared responsibility model in real. A further layer of complexity is added to cloud computing by necessitating providers and consumers to implement robust security measures. In this chapter, the most current strategies, technologies, and frameworks that can be used to secure data and networks within cloud environments will be discussed. Challenges will be considered that will provide a rational basis for achieving the appropriate level of assurance in the security of information systems and, as a consequence, the data they process, against confidentiality, integrity, and availability threats to evolve cyber threats. This will allow the organization to take full advantage of cloud computing, keeping compliance and information confidential and resilient against ever-changing cyber threats.